Determinant factor of anxiety disorders among bachelor degree students - Nurul Wahidatul Nasrah Saharudin; Fadhlin Mukhtarah Firdus; Nur Nabila Sabahul Khair; Tengku Henlysyafeena Fazira Tengku Abdullah; Siti Aminah Harun (Penerbit Universiti Kebangsaan Malaysia, 2020)
The demands of living nowadays cause a rising number people being diagnosed as having anxiety disorders and mental health problems. A survey done by National Health and Morbidity in 2019 finds that the prevalence of mental health problems among adults in Malaysia has increased from 8.9% in 2012, to 10.7% in 2015, to 31.1 % in 2019. These anxiety disorders share similar symptoms, like nervousness, irritability, insomnia and problems concentrating, but each has its own causes. One in 12 individuals in 2012 to one in six in 2018 cases reported are among Malaysian students. These results reveal a worsening state of mental health problems especially among students in Malaysia that must be addressed. Therefore, a preliminary study was conducted among students in one of the private college. The Depression and Anxiety Scale 21 (DASS-21) inventory was used to measure the students’ anxiety disorders based on three elements which are depression and anxiety. The results showed that the students are having moderate to very severe level of depression and anxiety. This finding is alarming in terms of increased risk for psychiatric morbidity because it indicates the amount of burden students have to bear in the current situation. Therefore, initiation of depression and anxiety management programs such as expanding counselling activities, providing adequate facilities and resources should be highly prioritized by authorities. Interview sessions are suggested to explore in depth on these issues.